2005
DOI: 10.1002/maco.200403823
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosioon resistance by sol-gel-based ZrO2-CeO2 coatings on magnesium alloys

Abstract: The physical, chemical and mechanical properties of magnesium alloys make them attractive materials for automotive and aerospace applications. However, these materials are susceptible to corrosion and wear. This work discusses the potential of using sol-gel based coatings consisting of ZrO 2 and 15 wt.% of CeO 2 . The CeO 2 component provides enhanced corrosion protection, while ZrO 2 impart corrosion as well as wear resistance. Coating deposition was performed by the dip coating technique on two magnesium all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 24 publications
(18 reference statements)
0
32
0
2
Order By: Relevance
“…Singh et al [28][29][30] observed a significant improvement in the corrosion and pitting resistances of sol-gel alumina coated low carbon steel, 9Cr 1Mo ferritic steel and 304 SS in highly corrosive NaCl solution. In comparison, relatively few study has been reported in the development of sol-gel based ceramic oxides coating on Mg alloys [31][32][33][34][35][36]. Phani et al [35] developed sol-gel ZrO 2 and ZrO 2 -CeO 2 coatings on Mg based AZ91D and AZ31alloys.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Singh et al [28][29][30] observed a significant improvement in the corrosion and pitting resistances of sol-gel alumina coated low carbon steel, 9Cr 1Mo ferritic steel and 304 SS in highly corrosive NaCl solution. In comparison, relatively few study has been reported in the development of sol-gel based ceramic oxides coating on Mg alloys [31][32][33][34][35][36]. Phani et al [35] developed sol-gel ZrO 2 and ZrO 2 -CeO 2 coatings on Mg based AZ91D and AZ31alloys.…”
Section: Introductionmentioning
confidence: 98%
“…In comparison, relatively few study has been reported in the development of sol-gel based ceramic oxides coating on Mg alloys [31][32][33][34][35][36]. Phani et al [35] developed sol-gel ZrO 2 and ZrO 2 -CeO 2 coatings on Mg based AZ91D and AZ31alloys. They found that both coated alloys showed superior corrosion performance in salt spray test.…”
Section: Introductionmentioning
confidence: 98%
“…Different additives have been used in the modification of silane films for improvement of their anti-corrosion properties in literatures (Shchukin, 2004, Kasten, 2006, Liu, 2006Phani, 2005and Pepe, 2001. Corrosion inhibitors, nanoparticle fillers, are doped into the silane coatings to enhance their corrosion resistant performance.…”
Section: Introductionmentioning
confidence: 99%
“…The most common precursors for the hybrid films preparation include: phenyl-trimethoxysilane (PTMOS), methyltriethisxysilane (MTEOS), 3-glycidoxypropyltrimethoxysilane (GPTMS), trimethoxysilyl-propyl-methacrylate (TSPM), methylmethacrylate (MMA) and methacylic acid (MA) [1][2][3][4][5][6][7][8][9][10], as well as mixtures of organically substituted and unsubstituted Si-alkoxides.…”
Section: Introductionmentioning
confidence: 99%